Performance of an interferon-γ release assay-based test for cell-mediated immunity to SARS-CoV-2 - Fonseca Brito, Luís; Tödter, Silvia; Kottlau, Julian; Cermann, Kathrin; Spier, Anthea; Petersen, Elina; Schäfer, Ines; Twerenbold, Raphael; Aepfelbacher, Martin; Lütgehetmann, Marc; Stahl, Felix R. (Frontiers in Immunology, 2023)
In search for immunological correlates of protection against acute coronavirus disease 2019 (COVID-19) there is a need for high through-put assays for cell-mediated immunity (CMI) to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We established an interferon-γ release assay -based test for detection of CMI against SARS-CoV-2 spike (S) or nucelocapsid (NC) peptides. Blood samples obtained from 549 healthy or convalescent individuals were measured for interferon-γ (IFN-γ) production after peptide stimulation using a certified chemiluminescence immunoassay. Test performance was calculated applying cutoff values with the highest Youden indices in receiver-operating-characteristics curve analysis and compared to a commercially available serologic test. Potential confounders and clinical correlates were assessed for all test systems. 522 samples obtained from 378 convalescent in median 298 days after PCR-confirmed SARS-CoV-2 infection and 144 healthy control individuals were included in the final analysis. CMI testing had a sensitivity and specificity of up to 89 % and 74 % for S peptides and 89 % and 91 % for NC peptides, respectively. High white blood cell counts correlated negatively with IFN-γ responses but there was no CMI decay in samples obtained up to one year after recovery. Severe clinical symptoms at time of acute infection were associated with higher measures of adaptive immunity and hair loss at time of examination. This laboratory-developed test for CMI to SARS-CoV-2 NC peptides exhibits excellent test performance, is suitable for high through-put routine diagnostics, and should be evaluated for clinical outcome prediction in prospective pathogen re-exposure.